Shariah auditing and Shariah compliance assurance in Malaysian Islamic banks - Sheikh Hassan, Ahmad Fahmi; Mohd Haridan, Nurfarahin (Universiti Sultan Azlan Shah, 2019)
Shariah committees (SCs) of Islamic banks have the crucial governance role of providing Shariah compliance assurance. In order to maintain the integrity of the bank in conforming with religious faith SBs should have the talent and others include contributing to Shariah audit task. To gain an in-depth understanding on the Shariah compliance audit role of SB, our present study has performed semi-structured intrerviews banks. Our study shows that the diverse Shariah and non-Shariah backgrounds of SB members could result in a more holistic view of Shariah issues, being more vocal in giving opinion and critism on the Shariah audit practices undertaken the existence of imbalance competency among SB members and the absence of proper Shariah audit framework in the two banks governance framework. As a result, most of the SB members delegate their Shariah audit role to be mainly performed by their Shariah audit division whose outcome will be submitted to them for approval. We argue that this passive role of SB members triggers concern on their independence and, consequently, compromised the Shariah compliance assurance provided to stakeholders.